DEVELOPMENT OF THE CONCEPT OF SOCIAL RIGHTS IN RUSSIA - Dmitry A. Sumskoy (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the definition of «social right», the content of social rights of citizens. Author proposed to social law as a separate branch of Russian law